ANALISIS YURIDIS TINDAK PIDANA ILLEGAL LOGING di KABUPATEN SIMALUNGUN: STUDI PUTUSAN NOMOR 495/PID, SUS-LH/2017/PN SIM - Surbakti, Anton Diary Steward; Syafitri, Syafitri; Hutasoit, Indra Abraham (JURNAL MUTIARA HUKUM, 2020)
This study aims to determine the juridical analysis of illegal loging in Simalungun Regency in accordance with decision number 495/Pid Sus-LH/2017/PN SIM, and to find out the prevention and eradication of forest destruction related to illegal loging. The research method in this journal is the type of juridical normative research which is descriptive in nature, juridical normative which refers to the legal norms contained in the statutory regulations relating to the crime of logging, descriptive data research is the disclosure of laws and regulations relating to legal theories which are the object of research. Data collection used in this research is to use literature study and decision study. All the data obtained will then be reviewed and analyzed then the data wiil be described qualitatively into descriptive which aims to describe the problem completely in order to reveal a truth. The problem in this research is how the juridical analysis of illegal logging in Simalungun Regency is in accordance with the decision number 495/Pid, Sus-LH/2017/PN SIM and how to prevent and eradicate forest destruction related to illegal loging. The solution is to increase the capacity of law enforcement officials and parties involved in preventing and eradicating and the role of the community in preserving forest. The conclusion is that the prevention and eradication of forest damage is part of forest protection activities in which the competent authorities participate in minimizing the eradication of illegal loging which is very detrimental to the nation and state.